Chemistry : - Kelter, Paul B. (Mc Graw-Hill, 2006)
Aimed at the non-science major, this text leads through real events in a familiar world. Each chapter moves from the macroscopic description of a familiar situation to the submicroscopic scale of the chemistry that underlies it. Once the chemistry is explained, the student is introduced to the environmental, economic, and social impact of that chemistry. Students are asked to critically examine the chemical choices available to individuals and society at large and to analyze the risks and benefits inherent in those choices.